Pemeriksaan Kesehatan, Pemberian Terapi Akupresur dan Edukasi Upaya Penatalaksanaan pada Pasien Hipertensi - Indaryani , Indaryani; Iskandar , Iskandar; Sari, Maritta; Sari, Nengke Puspita; Yani, Sutri; Darma, Dimas Dewa; Putri, Liza (Gayaku Publisher, 2024)
Hypertension is one of the non-communicable diseases that most people suffer from. Hypertension is known as the silent killer because this disease can cause death without causing symptoms because sufferers are not aware that they have hypertension. Headaches can result in poor blood circulation to the brain and if left untreated can cause stroke and even death. One effort to manage hypertension non-pharmacologically is acupressure therapy. Stimulation of acupressure points can stimulate the release of histamine as a mediator of blood vessel vasodilation. This process results in lowering blood pressure and headaches by causing vasodilation and decreasing blood vessel resistance. The community service methods used are education, blood pressure checks and providing acupressure therapy which will be carried out in RW 2, Sumber Jaya Village, Kampung Melayu District. After carrying out community service activities targeting people who took part in posbindu activities, the results showed that there was an increase in public knowledge about the management of hypertension and the application of acupressure therapy to reduce blood pressure and reduce coconut pain in hypertension sufferers. It is hoped that the public, especially hypertension sufferers, can apply acupressure therapy to lower blood pressure and reduce coconut pain in hypertension sufferers.